Effects of different antimalarial drugs on gametocyte carriage in P. vivax malaria. - Pukrittayakamee, S; Imwong, M; Singhasivanon, P; Stepniewska, K; Day, N; White, N (2008)
The gametocytocidal and asexual stage activities of eight antimalarial and eight antibiotic-containing regimens were evaluated in 349 adult patients with P. vivax malaria. Gametocytemia was found in 63% of patients (22% before and 41% after treatment). The median (range) gametocyte clearance time was 24 hours (range, 2-504 hours) and correlated with asexual parasite clearance time (r = 0.52, P < 0.001). Gametocytemia in vivax malaria was more common in patients with admission parasitemia > 10,000/microL and after treatment with drugs which have weak antimalarial activity, and was also associated with an increased rate of vivax reappearance (29.4% versus 14.1%, P = 0.002). Sexual stage activities corresponded with asexual stage activity for all tested regimens. Treatment with potent antimalarial drugs reduces the transmission potential of P. vivax.